Structural relationship among academic motivation, academic self‐efficacy, problem solving skills, creative thinking skills, and critical thinking skills - Orakci, Senol (Psychology in the schools, 2023)
This study investigates the structural relationship among academic motivation, academic self‐efficacy (ASE), problem solving skills (PSS), creative thinking skills (CRTS), and critical thinking skills (CTS). Structural Equation Model was utilized to compute the relationships between these variables. The sample of the study was comprised of 575 student teachers studying in Faculties of Education in Turkey in the academic year 2021–2022. The findings underline that academic motivation had a significant direct effect on CRTS and self‐efficacy had a significant direct effect on CRTS. In addition, the present study revealed that PSS had a significant direct effect on both creative thinking and CTS as well as revealing that creative thinking had a significant direct effect on CTS. Finally, in the present study, creative thinking significantly partially mediated the relationships between academic motivation, ASE, PSS, and CTS. These findings suggest implications for teacher training within the context of raising qualified teachers because the quality in the learning‐teaching process is positively expected to be influenced by the variables explored in the current study. Highlights Problem solving skills had a significant direct effect on both creative thinking and critical thinking skills. Creative thinking significantly mediated the relationship between academic motivation, academic self‐efficacy, problem solving skills, and critical thinking skills. Self‐efficacy had a significant direct effect on creative thinking skills.